ANALISIS SISTEM KEPEMIMPINAN DAN PELATIHAN DALAM MENINGKATKAN KINERJA KARYAWAN LAZISMU (Studi Kasus LAZISMU Kabupaten Mojokerto) - Yatun Ilmiyah, Chil; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2022)
In Indonesia, there are zakat management institutions, namely those established by the government such as BAZ (Badan Amil Zakat), and those formed by the community and protected by the government such as LAZ (Lembaga Amil Zakat). One example of LAZ is LAZISMU. In an organization or company, it is important to evaluate employees because the evaluation of future employee performance will be related to the development itself and career planning. One that can improve employee performance is a leadership and training system. The purpose of this study was to determine how the leadership and training system in improving the performance of LAZISMU employees, Mojokerto Regency. This research is qualitative research using phenomenological methods. The object of research is the head of the office and employees of LAZISMU, Mojokerto Regency. Data collection techniques in the form of observation, interviews, and documentation as well as the validity of the data using triangulation of data sources. The results of this study indicate that there are efforts made by LAZISMU related to the leadership system, namely shidiq, amanah, tabligh, and fathanah. And with training, namely coaching, assignments, temporary assignments, job instructions, and internships. Where this is an effort to improve employee performance.